Proceso de atención de enfermería en neonato pretermino con enterocolitis necrotizante. - Allico Morocho, Andrea Elizabeth (2020)
The present work leads to the creation of a clinical case with the topic NURSING CARE PROCESS IN PRETERM NEWBORN WITH NECROTIZING ENTEROCOLITIS. This case was presented at the Alfredo Noboa Montenegro General Hospital in the city of Guaranda de la Parroquia Veintimilla.To carry out the following clinical case, a diagnostic methodology was used where the patient's clinical history is known, the formulation of presumptive, differential, definitive and nursing data, follow-up and observations. In addition, the theoretical framework is deepened where information about the care of the newborn with necrotizing enterocolitis is investigated. Necrotizing enterocolitis continues to exist as one of the major undetermined difficulties in neonatal care. Despite the evolution in neonatal intensive care, it remains a dangerous disease. With the increase in survival of very low birth weight newborns, it emerges as a transcendental origin of neonatal mortality, being the most common cause of severe gastrointestinal disturbance in Neonatal Intensive Care Units. It affects about 10% of newborns weighing less than 1500g, with mortality rates of 50% or more, depending on the difficulty. Although it is true it is common in premature newborns, it can also be observed in term babies. Despite the massive inquiries on the subject over the last 30 years, its cause remains unknown. Early discovery through nursing assessment is important for prompt treatment. Clinical skills by the neonatal nurse or nurse are essential because the clinical signs of necrotizing enterocolitis can be minor or fatal.